Complex evaluation of the use of information technologies in the countries of eastern and central Europe - Ginevičius, Romualdas; Podvezko, Valentinas (Journal of Business Economics and Management, 2004)
“New economy” is a specific economic phenomenon emerging when two processes including globalization and technological revolution are taking place simultaneously. A question arises what economic and institutional conditions in the states under transition would allow them to take the best advantage of the potential of “new economy”. These conditions determine if a particular state is capable of accelerating its pace of long‐term economic development and approaching the level achieved by highly‐developed countries. In this context, the problem of evaluating the readiness of the states under transition to take advantage of “new economy” acquires great theoretical and practical value. To measure the above parameter, a so‐called indicator of new economy (NEI) based on ten variables characterizing the development and effective use of “new economy” has been recently offered. The INE indicator is a weighted sum of all ten variables for each state. It may also be calculated as a non‐weighted sum of all the related criteria. It may be assumed (based on the expertise) that the impact of any particular variable (criterion) on the general indicator of “new economy” varies to some extent, therefore, multiple criteria decision‐making methods should be used for complex evaluation of NEIFirst Published Online: 14 Oct 2010